Effects of Post-Fermentation Temperature on Amino Nitrogen Formation Kinetics and Physicochemical Properties of Bacterial-type Douchi from Different Soybean Varieties - LI Aijun, WANG Di, YANG Gang, SONG Jun, KONG Xiangbing, LIAO Shenglan, KAN Jianquan (Shipin Kexue, 2023)
In order to improve the quality stability of bacterial-type douchi during industrial production, four different varieties of soybean (LS, DBL, DBS and BS) were used to make bacterial-type douchi, and the modified Gompertz equation was used to fit the changes in the amino nitrogen content of bacterial-type douchi at three different post-fermentation temperatures (15, 25 and 40 ℃). Also, the free amino acid content was determined at the end of fermentation. The results showed that the Gompertz equation could well fit the kinetics of amino nitrogen formation (coefficient of determination > 0.96). The predicted fermentation endpoints at post-fermentation temperatures of 25, 15 and 40 ℃were approximately 9, 10, and 4 days, respectively. The maximum production of amino acid nitrogen in the four bacterial-type douchi at post-fermentation temperature of 15 ℃ decreased in the following order: DBL > LS > DBS > BS, while the maximum production of amino nitrogen at 25 and 40 ℃ decreased in the following order: LS > DBL > DBS > BS. The contents of amino nitrogen and free amino acids in black soybean douchi were significantly lower than those in yellow soybean douchi, but there was no significant difference among douchi from different yellow soybean varieties. After post-fermentation, the proportion of umami amino acids in the four bacterial-type douchi increased, and the proportion of bitter amino acids decreased. The proportion of umami amino acids in the four bacterial-type douchi at post-fermentation temperature of 40 ℃ decreased and the proportion of bitter amino acids increased compared with that at 15 ℃. This may be related to consumption of umami amino acids by the Maillard reaction at high temperatures. The correlation analysis of quality indexes shows that the trend of four bacterial-type douchi was similar. The results of this study can provide theoretical guidance for the industrial production of bacterial-type douchi.